2017
DOI: 10.1016/j.colsurfa.2017.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of polysulfone microcapsules containing tung oil in self-healing and self-lubricating epoxy coating

Abstract: :Polysulfone microcapsules containing tung oil were synthesized by a solvent evaporation method. The mean diameter and wall thickness of the synthesized microcapsules were approximately 130 μm and 9 μm, respectively. High thermal stability of the microcapsules with a thermal degradation onset temperature of 350°C was obtained. The multi-functional coating was fabricated by incorporating the microcapsules containing tung oil into an epoxy matrix. The self-healing and self-lubricating functions were evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…With the rupture of the shell materials during the sliding process, the lubricant in MCs flows to the contact surface and forms an oil film, reducing the friction coefficient of composites from 0.46 to 0.35 in the previous research . Compared to most polymers, the higher thermal conductivity of CFs (84.35 W/m°C) can effectively improve the heat dissipation rate of composites during the sliding process .…”
Section: Introductionmentioning
confidence: 93%
“…With the rupture of the shell materials during the sliding process, the lubricant in MCs flows to the contact surface and forms an oil film, reducing the friction coefficient of composites from 0.46 to 0.35 in the previous research . Compared to most polymers, the higher thermal conductivity of CFs (84.35 W/m°C) can effectively improve the heat dissipation rate of composites during the sliding process .…”
Section: Introductionmentioning
confidence: 93%
“…In general, there are two ways for core–shell particles to improve the tribological properties of the matrix: in the form of micro/nanocapsules and core–shell particles with solid cores. The commonly used method is micro/nanocapsules [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. The core–shell particles with solid cores to improve the tribological properties of solid matrix are less reported at present relatively.…”
Section: Applicationsmentioning
confidence: 99%
“…This could be attributed to the formation of a smooth layer between the friction pairs. Li et al [ 57 , 58 , 59 ] conducted a series of studies on microcapsules/epoxy resin composites and greatly improved the lubricating properties of the composite materials because of the newly formed oil film between the epoxy and sliding surface. What is more, they found that the wear debris of shells could act as liquid additives in the oil to improve the wear resistance of the composites.…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, we have demonstrated the encapsulation of a lubricant, ionic liquid and tung oil by solvent evaporation method. 18,25,26 Polysulfone (PSF) was used as the wall material of microcapsules and the synthesized microcapsules were applied in an epoxy resin to prepare self-lubricating and self-healing materials. PSF has high chemical and physical stability, excellent mechanical properties and thermal stability (its thermal decomposition temperature is 490-510 C).…”
Section: Introductionmentioning
confidence: 99%